Les paradoxes de la précarité dans l’emploi artistique. Le cas des musiciens professionnels au Mexique - Rocío Guadarrama (Revue Interventions Économiques)
This paper explores the dilemmas and ambiguity that the artist community faces in the current job market in Mexico, where precarious work conditions have become somewhat normalized. We selected a sample of professional musicians to investigate and unveil their challenging employment conditions that traditionally used to be more stable. These burdensome conditions permeating the job market are many times concealed under the false idea of “successful” multiple jobs holding. However, multiple job holding is far from being the normal working conditions imposed by employers or the social context that professional musicians should comply with.  It is rather a process and heterogeneous phenomenon with a strong subjective component. Based on this assumption, this research demonstrates the active role of musicians throughout their careers, as well as their employment strategies, resulting in a variable combination of jobs throughout their lives.